REPRODUCTIVE CHARACTERISTICS OF MODAL ECORACE OF REPRODUCTIVE CHARACTERISTICS OF MODAL ECORACE OF WILD TASAR SILKMOTH, ANTHERAEA PAPHIA LINN. IN DIFFERENT ALTITUDES OF SIMILIPAL BIOSPHERE RESERVE, ORISSA, INDIA - D. G. DEY; B. K. NAYAK; N. MOHANTY; B. C. GURU (The Bioscan, 2010)
The life cycle of Modal ecorace of wild tasar silkmoth, Antheraea paphia Linn. is trivoltine (TV), bivoltine (BV) and univoltine (UV) in lower, middle and higher altitude respectively in Similipal Biosphere Reserve. The life span in each stage (egg, larva, pupa, moth and diapause period) of life history of Modal ecorace increases irrespective of rearing season from lower altitude to higher altitude (i.e., from TV to UV form). The factors of reproductive efficiency (multiplication efficiency) such as percentage of pupal survivability, coupling, fecundity and hatching of eggs of this ecorace increase with an increase in altitude and from TV to UV form whereas the reverse trend is observed in the pupal mortality and juvenile mortality. The productive efficiency and commercial traits such as effective rate of rearing, cocoon weight, pupal weight, shell weight, shell ratio and total shell production of Modal ecorace are noticeably increased with increase in altitude in each crop season and from TV to UV type. The wide geographical condition with varying climatological parameters of Similipal Biosphere Reserve regulates the voltinism, the reproductive biology and economic traits and finally influences the population structure of the Modal ecorace of Antheraea paphia.